Brain-Derived Neurotrophic Factor Is Involved in Activity-Dependent Tonotopic Refinement of MNTB Neurons - Wollet, Mackenna; Kim, Jun Hee (Frontiers in Neural Circuits, 2022)
In the mammalian brain, auditory brainstem nuclei are arranged topographically according to acoustic frequency responsiveness. During postnatal development, the axon initial segment (AIS) of principal neurons undergoes structural refinement depending on its location along the tonotopic axis within the medial nucleus of the trapezoid body (MNTB). However, the molecular mechanisms underlying the structural refinement of the AIS along the tonotopic axis in the auditory brainstem have not been explored. We tested the hypothesis that brain-derived neurotrophic factor (BDNF) is a molecular mediator of the structural development of the MNTB in an activity-dependent manner. Using BDNF heterozygous mutant (BDNF+/−) mice, we examined the impact of global BDNF reduction on structural and functional development of MNTB neurons by assessing AIS structure and associated intrinsic neuronal properties. BDNF reduction inhibits the structural and functional differentiation of principal neurons along the tonotopic axis in the MNTB. Augmented sound input during the critical period of development has been shown to enhance the structural refinement of the AIS of MNTB neurons. However, in BDNF+/−mice, MNTB neurons did not show this activity-dependent structural modification of the AIS following repeated sound stimulation. In addition, BDNF+/- mice lacked a defined isofrequency band of neuronal activity following exposure to 16 kHz sound, suggesting degradation of tonotopy. Taken together, structural development and functional refinement of auditory brainstem neurons require physiological levels of BDNF to establish proper tonotopic gradients.